Pilihan Karier dan Disagregasi Karakteristik Demografis: Studi Minat Generasi Muda Bekerja di Sektor Agraris - Irwandi, Putra; Novita, Ninda; Kartika Sandra, Indah (Tunas Agraria, 2026)
Many factors currently cause the younger generation's low interest in working in the agricultural sector, even though this sector plays an important and strategic role in national economic development. This study aims to analyze the factors that influence the career choices of the younger generation to work in the agricultural sector by paying attention to the disaggregation of demographic characteristics. This study was conducted in September 2025 on 169 research respondents, namely agribusiness students and faculty of agriculture and forestry at Satya Terra Bhinneka University, purposively through filling out a Google form. The research variable used was interest as the dependent variable, while the independent variables consisted of age, gender, place of residence, parental occupation, parental land ownership, and work experience. Data analysis used binary logistic regression with the help of Microsoft Excel and STATA 17 software. The results showed that domicile, parental occupation, parental land ownership, and work experience had a significant effect on the interest of the younger generation in working in the agricultural sector. Therefore, relevant stakeholders are expected to increase exposure and direct experience for the younger generation in the agricultural sector through access to education, training, and agrarian entrepreneurship programs for future generations.   Rendahnya minat generasi muda bekerja di sektor agraris saat ini disebabkan oleh banyak faktor, meskipun sektor agraris ini memiliki peranan penting dan strategis dalam pembangunan perekonomian nasional. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi pilihan karier generasi muda untuk bekerja di sektor agraris dengan memperhatikan disagregasi karakteristik demografis. Penelitian ini berlangsung pada September 2025 terhadap 169 responden penelitian yakni mahasiswa Agribisnis, Fakultas Pertanian dan Kehutanan, Universitas Satya Terra Bhinneka secara purposive melalui pengisian google form. Variabel penelitian yang digunakan yakni Minat sebagai variabel dependen, sedangkan variabel independen terdiri umur, jenis kelamin, tempat tinggal, pekerjaan orang tua, kepemilikan lahan orang tua, dan pengalaman kerja. Analisis data menggunakan Regresi Logistik binner dengan bantuan softwere microsoft excel dan STATA 17. Hasil penelitian menunjukkan bahwa domisili tempat tinggal, pekerjaan orang tua, kepemilikan lahan orang tua, dan pengalaman kerja berpengaruh signifikan terhadap minat generasi muda bekerja di sektor agraris. Oleh karena itu, diharapkan peran stakeholder terkait, untuk dapat meningkatkan eksposur dan pengalaman langsung generasi muda di sektor agraris melalui akses pendidikan, pelatihan, dan program kewirausahaan agraris bagi generasi muda di masa mendatang